Survival estimates of bird species across altered habitats in the tropical Andes. Issue 2 (19th April 2019) - Tinoco, Boris A.; Graham, Laura; Astudillo, Pedro X.; Nieto, Andrea; Aguilar, Juan Manuel; Latta, Steven C.; Graham, Catherine H.
Abstract: The probability of long‐term persistence of a population is strongly determined by adult survival rates, but estimates of survival are currently lacking for most species of birds in the tropical Andes, a global biodiversity hotspot. We calculated apparent survival rates of birds in the Ecuadorian tropical Andes using a moderately long‐term (11 yr) capture–recapture dataset from three habitats that varied in how much they had been modified by human activities (native forest, introduced forest, and shrubs). We fit mark–recapture models for 28 species with habitat as a covariable. For all species, recapture rates between sampling sessions were low and varied from 0.04 for Rainbow Starfrontlets ( Coeligena iris ) to 0.41 for Stripe‐headed Brushfinches ( Arremon assimilis ) when averaged across all occupied habitats. Annual survival rates varied from 0.07 for Black‐crested Warblers ( Margarornis squamiger ) to 0.75 for Violet‐throated Metaltails ( Metallura baroni ). We found no significant differences in survival rates either among habitats or species grouped by habitat specialization. Because we found similar survival rates in native forest and human‐modified habitats, our results support those of recent studies concerning the potential value of secondary habitats for the conservation of some species of birds in the tropics. However, our conclusions are tempered by the uncertainty around the estimates of survival rates. Despite the relatively long‐term nature of our study, obtaining survival estimates for bird species in this region was challenging, and either more years of study or modification of field protocols may be needed to obtain more precise survival estimates. Resumen: Estimaciones de supervivencia de especies de aves a través de habitas alterados en los Andes tropicales La probabilidad de la persistencia a largo plazo de una población esta fuertemente determinada por las tasas de supervivencia de los adultos, sin embargo hacen falta las estimaciones de supervivencia para la mayoría de las especie de aves en los Andes tropicales, un hotspot de biodiversidad global. Calculamos las tasas de supervivencia aparente de aves en los Andes tropicales Ecuatorianos usando una base de datos de marca y recaptura de moderado largo plazo (11 años) en tres hábitats que variaron en el nivel de transformación por actividades humanas (bosque nativo, bosque introducido y matorral). Ajustamos modelos de marca recaptura para 28 especies con el hábitat como una co‐variable. Para todas las especies, las tasas de recaptura entre sesiones de muestreo fue baja y vario entre 0.04 en Coeligena iris y 0.41 en Arremon assimilis luego de promediar a través de los hábitats. Las tasas de supervivencia anual variaron entre 0.07 en Margarornis squamiger y 0.75 en Metallura baroni . No encontramos diferencias significativas en las tasas de supervivencia ni entre hábitats o entre especies agrupadas por especialización del hábitat. Debido a que encontramos tasas de supervivencia similares en bosque nativo y hábitats modificados por el hombre, nuestros resultados apoyan estudios recientes relacionados con el valor potencial de hábitats secundarios para la conservación de algunas especies de aves en los trópicos. Sin embargo, nuestras conclusiones son limitadas por la incertidumbre alrededor de las estimaciones de las tasas de supervivencia. A pesar de la naturaleza de largo plazo de nuestro estudio, obtener estimaciones de supervivencia para especies de aves en esta región es un reto y se requiere un mayor numero de años de estudio o una modificación en los protocolos de campo para obtener estimados de supervivencia mas precisos.